Die Sprache der Befreiung: Frauenbewegung im postkolonialen Frankreich - Oloff, Aline (transcript, 2018)
Libération des femmes: The "women's liberation"as an anti-colonial struggle for liberation. A contribution regarding the de-centering of "white"feminism.